Hamilton-Jacobi approach for first order actions and theories with higher derivatives - Bertin, M. C. [UNESP]; Pimentel, B. M. [UNESP]; Pompeia, P. J. [UNESP] (Academic Press Inc. Elsevier B.V., 2008)
In this work, we analyze systems described by Lagrangians with higher order derivatives in the context of the Hamilton-Jacobi formalism for first order actions. Two different approaches are studied here: the first one is analogous to the description of theories with higher derivatives in the hamiltonian formalism according to [D.M. Gitman, S.L. Lyakhovich, I.V. Tyutin, Soviet Phys. J. 26 (1983) 730; D.M. Gitman, I.V. Tyutin, Quantization of Fields with Constraints, Springer-Verlag, New York, Berlin, 1990] the second treats the case where degenerate coordinate are present, in an analogy to reference [D.M. Gitman, I.V. Tyutin, Nucl. Phys. B 630 (2002) 509]. Several examples are analyzed where a comparison between both approaches is made. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Hamilton-Jacobi formalism; singular systems; first order actions; higher order derivatives